Peran Penutur Asli dalam Meningkatkan Kemampuan Bahasa Arab Guru Perempuan di Modern Muslim Institute - Aina Salsabila Salsabila; Rauzatul Jannah Jannah (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2024)
Based on research at Al-Muslimun islamic boarding school, there are still many teachers who do not understand arabic languange. In this case the teachers must improve their arabic languange skills. One method to improve arabic languange skills for the teachers at Al-Muslimun islamic boarding school is to present the native speaker. This study aims to determine whether native speaker has a role in improving arabic languange skills for teachers at Al-Muslimun islamic boarding school. The research method used is qualitative descriptive. Data is collected through interview and observation, then reduced and presented the results, the last step taken is to conclude the data. The results show that native speaker has very significant role in improving arabic languange skills for teachers at Al-Muslimun islamic boarding school. In carrying out its role, of course there are several problems faced by both, native speaker and teachers. To overcome the problems, of course native speaker or teachers look for solutions.